Discourse analysis of students' interactions in terms of negotiation of meaning in the Malaysian context - Samani, Ebrahim; Noordin, Nooreen (IDOSI Publications, 2014)
Interaction is a process that facilitates second language acquisition. However, interaction per se does not lead to comprehension and it is believed that modifications to the structure of the interaction by moves to check or to seek, aid comprehension. The current study is aimed at determining students’ interactions, which were involved in negotiation of grammatical structures, in terms of types and frequencies of negotiation of meaning functions in Malaysian context. Participants of this study were 15 English as second language learners at Universiti Putra Malaysia (UPM). They were involved in a series of discussions over selected grammatical structures. Analysis of students’ chat logs was carried out through computer - mediated discourse analysis (CMDA). This study yielded 10 types of functions in negotiation of meaning, which are confirmation, confirmation check, elaboration, elaboration request, correction, clarification request, reply elaboration, comprehension check, reply clarification or definition, reply confirmation. According to the findings of this study, the most - frequently used functions were confirmation, confirmation check and elaboration and the least frequently used functions were reply confirmation, reply clarification and definition and comprehension check. However, due to lack of studies of similar nature, no comparison was made between findings of this study and the existing data in SLA. Findings of this study will add to teachers’ ever increasing array of options with which to meet the needs of students. With regard to current situation of Malaysia as the country with so many international students, future studies of these kinds can take into account the factors of proficiency, dyads, age and their effect on students’ interactions in terms of negotiation of meaning.